The role of environment in explaining frequency of participation of pre-school children in home and community activities. (15th March 2019) - Guichard, Sofia; Grande, Catarina
Abstract : Objectives: The main goal of the present study was to promote an understanding of the role of environment in explaining frequency of participation of pre-school children in home and community activities. Method: Parents of 116 children from completed an adapted version of the Young Children's Participation and Environment Measure (YC-PEM). Pre-school teachers assessed child functioning. Results: Maternal education was significantly related to the child's frequency of participation in home and community activities. Child functioning had an indirect effect on frequency of participation in home activities through perceived environmental barriers by parents. In the community setting, child functioning was a predictor of the parents' perception of environmental barriers and there was no evidence of a mediating effect of perceived environmental barriers. Conclusion: These findings highlight the importance of modifying specific environmental factors to promote child participation and functioning.